Pengaruh Promosi Dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Aplikasi Tokopedia Pada Produk Fashion Di Jakarta Barat - Sabrina Septia Rini; Warsono Warsono; Eka Putri Handayani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The growth of e-commerce has driven increased use of digital platforms for purchasing fashion products, making user satisfaction a crucial aspect of maintaining service sustainability. This study examines the impact of promotion and service quality on user satisfaction regarding fashion products on the Tokopedia app in West Jakarta. The research aims to determine the partial and simultaneous effects of promotion and service quality on user satisfaction. A quantitative approach using purposive sampling was employed. The sample consisted of 100 active Tokopedia users residing in the Kembangan, Kebon Jeruk, and Palmerah districts who had used the app for over three months and completed more than three fashion product transactions. Data were collected via Likert-scale questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination, with the aid of SPSS. The results indicate that promotion does not have a significant partial effect on user satisfaction (significance value 0.464 > 0.05). Service quality, however, has a positive and significant effect (significance value 0.000 < 0.05). Simultaneously, promotion and service quality significantly influence user satisfaction (significance value 0.000 < 0.05). An R² value of 51.9% indicates that these two variables explain 51.9% of the variation in user satisfaction, while the remaining 48.1% is influenced by other factors. This study contributes empirical evidence that service quality is the more dominant factor in enhancing user satisfaction with fashion products on Tokopedia in West Jakarta.